Agency and communication in IMF conditional lending: theory and empirical evidence - Silvia Marchesi; Laura Sabani; Axel Dreher (Center for Economic Studies and ifo Institute (CESifo), 2009)
We focus on the role that the transmission of information between a multilateral (the IMF) and a country has for the optimal design of conditional reforms. Our model predicts that when agency problems are especially severe, and/or IMF information is valuable, a centralized control is indeed optimal. To the contrary, when local knowledge is more important than the agency bias we expect delegation to dominate. Controlling for economic and political factors, our empirical tests show that the number of IMF conditions is lower in countries with a greater social complexity, while it increases with the bias of the countries' authorities, openness, and transparency, consistently with the theory.
Keywords: C23; D82; F33; N2; 330; IMF conditionality; delegation; communication; panel data; Anpassungsprogramm des IWF; Internationaler Kredit; Informationsverhalten; Kommunikation; Agency Theory; Theorie; Welt; Entwicklungsländer